2010
DOI: 10.1111/j.1365-3083.2010.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Frequency of Peripheral Blood Lymphocyte Subpopulations in Severe Traumatic Brain‐Injured Patients

Abstract: Infections are leading causes of increased morbidity and mortality of severe traumatic brain‐injured (STBI) patients. The mechanism underlying the susceptibility to the infections is still unexplained. The purpose of the study was to investigate changes in frequency of leucocytes subpopulations in peripheral blood of patients with STBI during the course of intensive care treatment. Twenty patients with STBI were included in the study. Healthy age‐ and sex‐ volunteers served as control. Peripheral blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 24 publications
7
50
3
Order By: Relevance
“…The incidence of infection following TBI is obviously higher than other noncranial insults such as polytrauma, burn injury, and major surgery [6]. This increased incidence of infection is attributed mainly to the systemic immune suppression arising directly from TBI [7], a view strengthened by recent studies that have provided evidence to clarify the alteration of the humoral or cellular immunity following TBI [8-11]. Though these studies have demonstrated novel changes in the composition and function of the immune system after TBI, the mechanisms responsible for TBI-induced immune dysfunction are still not well-understood and need to be further investigated.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The incidence of infection following TBI is obviously higher than other noncranial insults such as polytrauma, burn injury, and major surgery [6]. This increased incidence of infection is attributed mainly to the systemic immune suppression arising directly from TBI [7], a view strengthened by recent studies that have provided evidence to clarify the alteration of the humoral or cellular immunity following TBI [8-11]. Though these studies have demonstrated novel changes in the composition and function of the immune system after TBI, the mechanisms responsible for TBI-induced immune dysfunction are still not well-understood and need to be further investigated.…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies have demonstrated that patients with severe TBI experience a significant reduction in the frequency and number of CD4 + and CD8 + T cells in the peripheral blood, which mainly occurs within 24 h after trauma [8, 34, 35]. However, it was thought that severe TBI has no influence on the biology of B cells, based on the evidence provided by several studies indicating that the number and frequency of B cells does not change after injury [8, 34, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown a reduced NKCA of blood NK cells of patients with spinal cord injury and TBI (61)(62)(63). Although the CD56 bright population stayed unchanged, the CD56 dim subtype was decreased, and this correlated with the occurrence of infections after TBI (64). Alternatively, in the context of stroke, the NK cell counts showed a nonsignificant decrease (65-67).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 97%
“…In traumatic brain injury, patients' peripheral blood CD56 bright subset did not fluctuate during the course of intensive care treatment (7 d) (53).…”
Section: Cd56mentioning
confidence: 99%